FATHERâS ROLES ON THE EXCLUSIVE BREASTFEEDING PRACTICE - Arifah, Izzatul; Rahayuning P, Dina; Rahfiludin, Moh. Zen (Universitas Ahmad Dahlan, 2014)
Background:Exclusive breastfeeding is the best way feed infant aged 0-6 months. Various factors influence breastfeeding practice, include fatherâs role factors. This study aimed to describe fatherâs roles and its association to breastfeeding practices.Method: Method used in this study was survey with cross sectional approach. The sample were 80 couples who had 0-6 month aged baby lived in the service area of Ngesrep subdistrict in February 2012 using pusposive sampling technique. Data were analyzed descriptively using chi-square statistical test.Result: The result showed among mothers with exclusive breastfeeding practice, about 80% father did support their wife. Fatherâs role were significantly associated to exclusive breastfeeding practices ( =0.0001). It was also influenced by medical support ( =0.042), grand mother and peer support ( =0.0001), and non-working mothers ( =0.049).Conclusion: Fathers who did role supporting mothersÂ to practice exclusive breastfeeding, improve its success. However, medical support, grand mother and peer support, and motherâs occupation are confounding variable for this.Â Keywords: exclusive breastfeeding, father, fatherâs roleÂ